Pengaruh Perilaku Kewirausahaan Terhadap Kinerja Usahatani Kopi Organik di Kabupaten Sumbawa (Jurnal Agribisnis Indonesia, 2024)
Coffee is an important plantation commodity for Indonesian economy. Market demand is an opportunity to improve the performance of coffee farming, especially organic coffee. Success in farming is driven by individual and environmental factors such as farmer competency, cultivation techniques, facilities and infrastructure, and post-harvest handling. Farmer’s' success is influenced by internal factors, That is entrepreneurial behavior. This research aims to identify individual characteristics, analyze individual and environmental factors on entrepreneurial behavior, as well as the influence of entrepreneurial behavior on the performance of organic coffee farming. The number of respondents taken using the census method was 180 farmers. Data analysis using SmartPLS 3.0. The research results show that the age characteristics of farmers are 45–56 years with quite a long experience. Most of the farmers are elementary school graduates, and the owning of land area is 0-1 hectare. Individual and environmental factors have a positive and significant influence on entrepreneurial behavior, the most dominant indicators are farming scale and perception. The most dominant indicators of environmental factors are the availability of input materials and solidarity between farmers. Entrepreneurial behavior also has a positive and significant effect on farming performance with the most dominant indicators being diligent farming and the courage to take risks. This shows that entrepreneurial behavior can improve the performance of organic coffee farming. Optimizing the entrepreneurial behavior of organic coffee farmers can be done by increasing farmer capacity, as well as government support in cilities and infrastructure for farmers to support farming activities.